ANALISIS FAKTOR YANG MEMPENGARUHI KONSUMEN LEBIH MEMILIH BERBELANJA DI HYPERMART MALL SKA KOTA PEKANBARU - Devi Novianti Devi Novianti; Gusnardi '; RM. Riadi RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Price, product, location and service quality are some of the factors that influence consumers choose to shop in a shopping center market both traditional and modern markets in general. Learn about consumer behavior can determine how consumers make purchasing process and purchasing process again. This study aims to determine the factors that influence consumers prefer shopping at Hypermart Mall SKA Pekanbaru. The method used is descriptive quantitative method. The population in this study are all consumers who happened to be shopping at Hypermart Mall SKA Pekanbaru by Acidental Sampling and sample use of the 100 respondents. The data used is primary data that questionnaires filled out by respondents and secondary data obtained through Hypermart Mall SKA Pekanbaru, literature from books, literature and the internet. From the results of this study concluded that: (1) the price, product, location and service quality factors simultaneously affect the decision to shop at Hypermart Mall SKA Pekanbaru. (2) Hypermart Mall SKA Pekanbaru has a price, product, location and service quality that allows a customer to make a decision to shop at Hypermart and not only that there are other factors even called smart consumers. Keywords : price, product, location, service quality and shopping decisions.